Stress intensity factors of cracks in tapered lug - Ma, Ying Shu (2015)
This project aims to determine the stress intensity factors, KI of cracks in tapered lug with a hole. These factors are used to predict the crack growth and also the life of structure connected with a tapered lug. By using an commercially available finite element software called ANSYS, a tapered lug with a hole was modelled and analysed. Through thickness cracks were prescribed at the edges of hole. Stress intensity factors, KI were computed for different crack length “c”, and for plane stress and plane strain conditions. Two different loading conditions were also imposed and analysed: point load and pressure load. From the stress intensity factors KI, the geometrical factor β result can be extracted and compared with available theoretical results. For practical considerations, the results of stress intensity factors in plane strain condition and with pressure loading condition are recommended as they would best represent the real situation of structural application.